Francis Bacon - Alley, Ronald; Rothenstein, John (London : Thames and Hudson London, 1964)
This, the first book on Francis Bacon, is a well-documented study of his life and work, and is likely to remain the basic, indispensable monograph. The catalogue raisonné by Ronald Alley, Deputy Keeper of the Tate Gallery, includes reproductions of all his surviving paintings, and even of some of the most important destroyed pictures, and makes it possible as never before to see his whole development from 1929 up to the summer of 1963. Many new facts have come to light, particularly about his early career, and a number of widely held ideas about his paintings are shown to be based on a complete misinterpretation.
bibliog. p. 281-288
biog. p. 275-278
ind. tent., filmog. p. 279-280
Engels
boek
Keywords: Bacon, Francis